A Protocol for Diagnosis and Management of Aortic Atherosclerosis in Cardiac Surgery Patients - Wouter W. Jansen Klomp; George J. Brandon Bravo Bruinsma; Arnoud W. J. Van ’t Hof; Jan G. Grandjean; Arno P. Nierich (International Journal of Vascular Medicine)
In patients undergoing cardiac surgery, use of perioperative screening for aortic atherosclerosis with modified TEE (A-View method) was associated with lower postoperative mortality, but not stroke, as compared to patients operated on without such screening. At the time of clinical implementation and validation, we did not yet standardize the indications for modified TEE and the changes in patient management in the presence of aortic atherosclerosis. Therefore, we designed a protocol, which combined the diagnosis of atherosclerosis of thoracic aorta and the subsequent considerations with respect to the intraoperative management and provides a systematic approach to reduce the risk of cerebral complications.